A health related quality of life assessment in treated head and neck cancer patients in east coast of Malaysia - Abdullah, Kahairi (2006)
INTRODUCTION Length of survival and tumour recurrence has long been used as the assessment of treatment outcome in Head and Neck cancer patients. However for the past 20 years with reduction in tumour recurrence and increasing survival rates, quality of life (QOL) of the survivors has becoming the measure of treatment outcome. Recent data from United State indicated that the number of patients with Head and Neck cancer is increasing over the years and the trend is probably similar in Malaysia. QOL is a broad concept which covers four essential components which are physical function, psychological state, social interaction and somatic sensation. There are many validated instruments available worldwide and the University of Washington quality of life (UWQOL) questionnaire is the most commonly used in United Kingdom as well as United States. As in other parts of the world, there has been an increasing demand for Malaysian researchers nowadays to assess the QOL in their Head and Neck cancer patients. OBJECTIVES The main objective in this study is to evaluate quality of life in the treated Head and Neck cancer patients. METHODOLOGY This is a cross-sectional study in a treated Head and Neck cancer patients conducted in Ear, Nose and Throat clinic (ENT) of Hospital Tengku Ampuan Afzan (HTAA) Kuantan in the state of Pahang and ENT clinic of Hospital Universiti Sains Malaysia (HUSM) Kubang Kerian in the state of Kelantan. Those Malay patients who fullfilled the inclusion and exclusion criteria were recruited into this study. Standard validation process were followed which include forward and backward translation of the originial version UWQOL. Patients were asked to answer the Malay version UWQOL. Data were analysed using statistical software SPSS version 12.0 for Windows. RESULTS Reliability was tested by inter-item correlation coefficient with Cronbach' s alpha value of 0.80. Test-retest reliability as reflected by intraclass correlation coefficient was 0.85. Patients with early stage tumour (stage I and II) tend to score higher than advance stage tumour (III and IV). Site of tumour and mode of treatment does not significantly affect the patients QOL. CONCLUSION This data suggest that Malay version of UWQOL is reliable and valid qestionnaire when applied to a sample of Head and Neck cancer patients in Malaysia. Tumour stage was the strongest determinant of quality of life in Head and Neck cancer patients.